KARAKTERISTIK BIOMASSA DAUN BUNGA SEPATU MENJADI BAHAN BAKAR STERNO GEL - Muyassaroh; Jimmy; Dewi, Rini Kartika (Teknik Kimia ITN Malang, 2021)
Sterno gel of hibiscus leaves (Hibiscus rosa-sinensis L.) is an alternative energy source that can be used as fuel because it has non-volatile characteristics, during the combustion process it does not smoke, does not have soot and does not produce harmful and carcinogenic gas emissions and does not have any harmful gases. the impact of emissions on the environment, Inside the hibiscus leaf contains saponins, -sitosterol, stigmasterol, taraxeryl acetate and 3-cyclopropane and their derivatives which will dissolve in both water and ethanol and will form colloids in water. With this composition, the researchers used hibiscus leaf biomass as fuel for sterno gel, where in this study the variables were filtrate mass of hibiscus leaf :10,1 20, 30, 40,50,60 and 70 grams and mass of carbopol :1, 1.5, 2 and 2.5 grams. From the research, it was found that the best burning time was 60 grams of hibiscus filtrate mass and 2.5 grams of carbopol mass, which was 25.02 minutes with the resulting gas emission values ​​of NOx: 4 ppm, SO2: 3 ppm and H2S: 2 ppm. While the calorific value is 3500 calories.